The Myth of Luang Phrabang and the Construction of Cultural Landscape - Phetsamai, Somsack; VONGPHACH, Phitsaphong; SOUKCHALUEN, Phatsada; PANYAVONG, Sommor; PHENGPHANYA, Phone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This article presents a study on Luang Prabang legends and their articulation of the cultural landscape. The objective of the research is to analyze the content of these legends, which describe the historical settlement of villages and towns, the identification of sacred sites and the organization of traditional ritual ceremonies, as well as the natural features embedded within the Luang Prabang narrative tradition. The concept of cultural landscape in the context of the Luang Prabang legends can be understood through three main thematic categories found across ten core stories. First, the legends describe the settlement of villages, such as the Chanthaphanith legend, the naming of Xieng Thong, the founding of Xieng Thong City, and the establishment of communities along the Mekong River and the Khan River. Second, they portray sacred places and traditional ceremonies, exemplified by the stories of the Fifteen Naga Clans and the Forty Naga Clans. Third, the legends narrate the origins of natural features, such as in the story of Mount Phou Nang.